PENGAMANAN PESAN RAHASIA MELALUI KRIPTOGRAFI VIGENERE CIPHER DENGAN KUNCI BERLAPIS - Benni Purnama (JURNAL AKADEMIKA)
Techniques Vigenere cipher alphabet cipher is a type of compound that is the most simple. Vigenere cipher applying poly alphabetic substitution method and belongs to the category in which the key is a symmetric key used for encryption is the same as the key used for the decryption process. In carrying out the method of encryption is done with the help of table vigenere tableau. Advantages of vigenere cipher of previous classical methods (Caesar cipher) that is polyalphabetic substitution for ciphrenya, where the same character has a different character substitution. However, the method vigenere However, there are some weaknesses such as the plaintext character A always get the same characters between the key and the character key and cipherteksnya experiencing continuous repetition of the same, giving rise to the same ciphertext to plaintext pieces where its position is a multiple of the key length so that the plaintext will always get the same piece for the encryption key. To avoid the drawbacks mentioned above, the need for techniques for increasing the strength of the results of this vigenere chiperteks. One of them is to make more than one key. With more than one dibuatkanya key (key-plated) which in this study the authors tried to make three key layers, the weakness that has been described as the author of the above can be resolved. The results of this study found that It is because of padded keys made ​​as many as three, while the cryptanalyst can guess that the key is created in the example above is the default key that is only one layer only and generate plaintext which still can not be read.